IMPLEMENTASI PEMBINAAN PRA NIKAH DALAM PENURUNAN PERCERAIAN DI KANTOR URUSAN AGAMA (KUA) KECAMATAN DIWEK KABUPATEN JOMBANG 2022-2023 - Maftuh Al-Fikri Rosyadi; Ahmad Faruq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Marriage is an important milestone in human life, which brings together two individuals with diverse backgrounds, values and dreams to build a happy and harmonious family. However, the high divorce rate in many countries, including Indonesia, shows how complex the challenges are in maintaining household integrity. The type of research used is field research.The results of this research can be concluded that: The implementation of Pre-Wedding Development in KUA Diwek District is not just a series of learning sessions, but also a means to prepare the prospective bride and groom holistically. This premarital coaching program provides an in-depth understanding of the importance of building a harmonious household and prepares the prospective bride and groom mentally and emotionally through coaching and hypnotherapy materials.